2021
DOI: 10.2147/cmar.s298619
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Pattern at 18-Month Post-Diagnosis and Outcomes of Breast Cancer Among Chinese Women with Early-Stage Breast Cancer

Abstract: Background Evidence of the association between dietary pattern and outcomes of breast cancer was limited in Asian women, including Chinese. Patients and Methods A prospective cohort study was initiated among Chinese breast cancer patients to investigate lifestyle habits and outcomes of breast cancer. At each follow-up, validated food frequency questionnaires (FFQ) were used to assess patients’ dietary intake. This study included 1226 patients with invasive early-stage b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 34 publications
(46 reference statements)
1
9
0
Order By: Relevance
“…The relationship between dietary patterns and BC prognosis has been studied in four countries, particularly focusing on healthy, Mediterranean, and DASH diets. Two studies on healthy eating patterns conducted in the United States found that this pattern had the potential to reduce patient mortality (64, 65), while two studies in China found no such relationship (66,67).…”
Section: Dietary Patterns and Prognosis Of Bcmentioning
confidence: 99%
“…The relationship between dietary patterns and BC prognosis has been studied in four countries, particularly focusing on healthy, Mediterranean, and DASH diets. Two studies on healthy eating patterns conducted in the United States found that this pattern had the potential to reduce patient mortality (64, 65), while two studies in China found no such relationship (66,67).…”
Section: Dietary Patterns and Prognosis Of Bcmentioning
confidence: 99%
“…The Prudent diet in the Life After Cancer Epidemiology study, and the Western diet in the Nurses' Health Study were negatively and positively associated, respectively, with all‐cause mortality, but not with breast cancer mortality 51,52 or recurrence 52 . Neither of these dietary patterns were associated with breast cancer prognosis in the Hong Kong NTEC‐KWC Breast Cancer Survival Study 53 …”
Section: Resultsmentioning
confidence: 93%
“…Tables S6 and S7 show the characteristics and main results of the studies identified investigating data driven or predefined dietary and lifestyle patterns 6,34‐56 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations